Peranan Diagnostik Teknik Imunofluoresensi Dalam Dermatologi - Hardyanto, Hardyanto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1980)
Diagnostic procedures by means of immunofluorescence techniques have been greatly used in investigations of some diseases which have immunologic background. These tests are now accepted as routine diagnostic procedures in dermatology in advanced countries beside electron microscopy. The main purpose of this paper is to summarize intelligibly immunofluorescence results obtained so far in various skin disorders. The methods of application can be divided into direct and indirect method.The basic principle, technical procedures, some problems and application of immunofluorescence on various skin diseases are discussed.Key Words: immunofluorescence techniques - direct and indirect immunofluorescence -- antigen-antibody tracing - immunologic skin diseases - dermatoses